2023
DOI: 10.3399/bjgp.2022.0518
|View full text |Cite
|
Sign up to set email alerts
|

GPs’ and pharmacists’ views of integrating pharmacists into general practices: a qualitative study

Abstract: Background: Practice-based pharmacists (PBPs) have been introduced into general practice across the United Kingdom (UK) to relieve some of the pressures within primary care. However, there is little existing UK literature that has explored healthcare professionals’ (HCPs’) views about PBP integration and how this role has evolved. Aim: To explore the views and experiences of GPs, PBPs, and community pharmacists (CPs) about PBPs’ integration into general practice and their impact on primary healthcare delivery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…A similar suggestion was previously made regarding a universal system of communication between pharmacists and other primary healthcare providers to improve workflow processes and improve community-based care [ 35 ]. In addition, a qualitative study exploring GPs and pharmacists’ views on integrating pharmacists into general practice emphasised a need to have direct access to GPs [ 36 ]. Therefore, this shows the challenges faced by pharmacists in communicating with GPs and other primary healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…A similar suggestion was previously made regarding a universal system of communication between pharmacists and other primary healthcare providers to improve workflow processes and improve community-based care [ 35 ]. In addition, a qualitative study exploring GPs and pharmacists’ views on integrating pharmacists into general practice emphasised a need to have direct access to GPs [ 36 ]. Therefore, this shows the challenges faced by pharmacists in communicating with GPs and other primary healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 pandemic, the role of community pharmacists has evolved rapidly from a service for dispensing medicines to one that actively participates in the treatment of patients by providing key health services and advice to the public [ 63 ]. In several countries, such as Australia [ 64 ] and the UK [ 65 ], there has been some integration of pharmacists into general practice, which has been shown to help optimize prescribing and health outcomes in patients with polypharmacy, as well as to reduce inappropriate prescribing [ 66 ]. With ever-increasing pressure on primary care services, this is a move that is broadly welcomed by GPs, especially with regard to medicine optimization [ 67 ].…”
Section: Role Of the Pharmacistmentioning
confidence: 99%
“…A recent study in Northern Ireland also found that pharmacists not employed by the practice faced some difficulty reconciling competing demands from both employers and practice hosts [25].…”
Section: Strengths and Limitationsmentioning
confidence: 99%